Choosing Therapy: A Guide to Getting What You Need - Romanovsky, Ilyana (Rowman & Littlefield Publishers, 2013)
Like any decision that we make in life, making the choice to seek therapy involves mastering a large body of knowledge, sifting through the thousands of therapists in the field and finding the right one, understanding different psychological approaches to counseling and what might work best for any one person, learning a variety of skills on how to be in therapy, and exploring one’s most inner self with a complete stranger. Most people are unfortunately stuck navigating this difficult process on their own, leaving a lot of things up to chance. Choosing Therapy acknowledges these difficulties and offers readers the tools they’ll need to choose the right therapist, set their goals for therapy, and understand the benefits and outcomes available to them through the various approaches therapists take. When entering therapy,individuals may not be armed with the information they need in order to make progress and see results. Many stop therapy if they don’t feel they are getting anything out of it; others stop if they feel they are being treated differently by others who know they are in therapy. In Choosing Therapy, Ilyana Romanovsky clearly defines various psychological approaches therapists take, the different types of therapies available including long terms versus short term and group versus individual therapy, and ways of overcoming stigma associated with being in counseling. She discusses various psychotherapeutic medications and other questions patients might have about the ways they might address the issues they experience. Helping readers to define goals, understand treatment options, and prepare to do the work of therapy, Romanovsky offers a clear roadmap to those new to treatment, to those returning to treatment, and to those helping others to seek treatment.